ISLAMIC BUSINESS COMMUNICATION ETHICS - Elida Elida; Vera Ayu Oktaviasari; Iyad Abdallah Al- Shreifeen (Review of International Economy and Finance, 2024)
Islamic business communication ethics is an important study that combines the principles of effective communication with Islamic ethical values. In a business context, good communication does not only focus on delivering clear messages but must also reflect honesty, fairness, and social responsibility as stipulated in Islamic teachings. This study aims to explore how Islamic ethics can be applied in business communication to enhance trust and good relations between the parties involved. The literature research method is used to collect and analyze various related sources including the Quran, Hadith, and contemporary literature on business ethics and communication. The results of this study indicate that by adopting Islamic ethics in business communication, companies can not only achieve their commercial goals effectively but also build a good and sustainable reputation in society. This study emphasizes the importance of integrating Islamic values in modern business operations to create an ethical and harmonious work environment.